Antibiotic cement was associated with half the risk of re-revision in 1,154 aseptic revision total knee arthroplasties - Bini, Stefano A (Acta Orthop, 2016)
BACKGROUND AND PURPOSE: Aseptic revisions comprise 80% of revision total knee arthroplasties (TKAs). We determined the incidence of re-revision TKA, the reasons for re-revision, and risk factors associated with these procedures. PATIENTS AND METHODS: We conducted a retrospective cohort study of 1,154 patients who underwent aseptic revision TKA between 2002 and 2013 and were followed prospectively by a total joint replacement registry in the USA. Revision was defined as any operation in which an implanted component was replaced. Patient-, surgeon-, and procedure-related risk factors were evaluated. Survival analyses were conducted. RESULTS: There were 114 re-revisions (10%) with a median time to reoperation of 3.6 years (interquartile range (IQR): 2.6–5.2). The infection rate was 2.9% (34/1,154) and accounted for 30% of re-revisions (34 of 114). In adjusted models, use of antibiotic-loaded cement was associated with a 50% lower risk of all-cause re-revision surgery (hazard ratio (HR) = 0.5, 95% CI: 0.3–0.9), age with a 20% lower risk for every 10-year increase (HR = 0.8, CI: 0.7–1.0), body mass index (BMI) with a 20% lower risk for every 5-unit increase (HR = 0.8, CI: 0.7–1.0), and a surgeon’s greater cumulative experience (≥ 20 cases vs. < 20 cases) with a 3 times higher risk of re-revision (HR = 2.8, CI: 1.5–5). INTERPRETATION: Revised TKAs were at high risk of subsequent failure. The use of antibiotic-loaded cement, higher age, and higher BMI were associated with lower risk of further revision whereas a higher degree of surgeon experience was associated with higher risk.